(untitled) (The Review of Diabetic Studies, 2022)
OBJECTIVE: Our objective was to determine the trend and precipitating factors of the severity of diabetic ketoacidosis (DKA) in the population admitted to the Pediatric Intensive Care Unit (PICU) in a large teaching hospital in the Eastern region of Saudi Arabia. METHODS: We conducted a retrospective, analytical study at King Fahad Hospital, Imam Abdulrahman Bin Faisal University, Alkhobar, Saudi Arabia. We retrieved the complete medical records of 2234 children who were admitted to the PICU during the 10-year period of 2010 through 2019. The children included those with polydipsia, polyurea, abdominal pain, vomiting, dehydration, and weight loss, as well as breathing disturbances due to acidosis and CNS issues such as lethargy or coma and elevated blood glucose level, > 200 mg/dL [> 11.1 mmol/L], venous pH 7.3, serum total CO2 15 mmol/L, and bloodhydroxybutyrate concentration 3 mmol/L or moderate or severe ketonuria. RESULTS: Out of 2234 PICU admissions, 211 (9.4%) were diagnosed with DKA. A persistent increase in the rate of DKA ended up at 14.1% in 2019 (p = .005). The incidence of DKA was 88/2234 (3.93%). The severity of DKA was as follows: 130 (61.6%) had severe and 81 (38.4%) had moderate DKA. Excessive sweet intake without adding insulin in 83 (39.3%) patients and unhealthy lifestyles (35.1%) were the best predictors of severe DKA (p = .001). CONCLUSION: Over a 10-year period, the DKA pattern was persistently rising and slightly falling, which ended up at the significantly highest rate of 14.1% in 2019. URTI, pneumonia, unhealthy lifestyle, and excess sweet intake were significant precipitating factors associated with severe DKA.